2014
DOI: 10.1016/j.fgb.2014.05.005
|View full text |Cite
|
Sign up to set email alerts
|

The proteome and phosphoproteome of Neurospora crassa in response to cellulose, sucrose and carbon starvation

Abstract: Improving cellulolytic enzyme production by plant biomass degrading fungi holds great potential in reducing costs associated with production of next-generation biofuels generated from lignocellulose. How fungi sense cellulosic materials and respond by secreting enzymes has mainly been examined by assessing function of transcriptional regulators and via transcriptional profiling. Here, we obtained global proteomic and phosphoproteomic profiles of the plant biomass degrading filamentous fungus Neurospora crassa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
63
0
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 66 publications
11
63
0
5
Order By: Relevance
“…Although there are several highly conserved nutrient-sensing pathways that have been implicated in the lignocellulosic response, their role in the regulation of plant cell wall degrading enzyme transcription is still unclear. For example, the TOR complex is involved in nutrient sensing in eukaryotes and has been shown to be highly phosphorylated under cellulolytic conditions in N. crassa (Wullschleger et al, 2006;Xiong et al, 2014a). Putative ubiquitination and deubiquitination enzymes, such as CreB/CRE-2 and CreD, have been implicated in CCR and glycosyl hydrolase production potentially through ubiquitination of CreA itself, however, additional protein targets and the precise mechanism of action of the genes involved has yet to be identified (Boase and Kelly, 2004;Colabardini et al, 2012;Denton and Kelly, 2011;Kelly, 2001, 2002;Ries et al, 2016;Xiong et al, 2014b).…”
Section: Other Factors Involved In Carbon Catabolite Repressionmentioning
confidence: 99%
“…Although there are several highly conserved nutrient-sensing pathways that have been implicated in the lignocellulosic response, their role in the regulation of plant cell wall degrading enzyme transcription is still unclear. For example, the TOR complex is involved in nutrient sensing in eukaryotes and has been shown to be highly phosphorylated under cellulolytic conditions in N. crassa (Wullschleger et al, 2006;Xiong et al, 2014a). Putative ubiquitination and deubiquitination enzymes, such as CreB/CRE-2 and CreD, have been implicated in CCR and glycosyl hydrolase production potentially through ubiquitination of CreA itself, however, additional protein targets and the precise mechanism of action of the genes involved has yet to be identified (Boase and Kelly, 2004;Colabardini et al, 2012;Denton and Kelly, 2011;Kelly, 2001, 2002;Ries et al, 2016;Xiong et al, 2014b).…”
Section: Other Factors Involved In Carbon Catabolite Repressionmentioning
confidence: 99%
“…The MAPK phosphorylation site (amino acid S73) is marked by a yellow box and underlined. The 23 additional phosphorylation sites (T39, T43, T46, S47, S49, S61, S63, T65, S66, S73, T91, Y95, S345, S352, T357, S436, T496, S510, S538, S542, T550, T555, and S558) are marked in blue (Jonkers et al 2014) and green boxes (Xiong et al 2014). (B) HAM-14-GFP localizes in the cytoplasm and occasional puncta in communicating germlings (white arrow).…”
Section: Ham-14 Binds the Map Kinase Cascade Members Mek-2 And Mak-2mentioning
confidence: 99%
“…Eight HAM-14 phosphopeptides were detected in our phosphoproteomics experiments (Jonkers et al 2014); one phosphopeptide has a MAPK consensus site, while two additional phosphopeptides have a degenerate MAPK consensus site (pS/pT-P). From a subsequent phosphoproteomic study on N. crassa hyphal cultures (Xiong et al 2014), an additional 33 phosphopeptides were identified for HAM-14. Thus, 24 possible unique phosphosites are present in HAM-14.…”
mentioning
confidence: 99%
“…In the fungus Fusarium graminearum, 2,902 putative phosphopeptides on 1,496 different proteins were identified (23). Phosphoproteomics data sets for the fungi Cryptococcus neoformans (24), Aspergillus nidulans (25), Alternaria brassicicola (26), Botrytis cinerea (26), Neurospora crassa (27), and Schizosaccharomyces pombe (28) have also been published.…”
mentioning
confidence: 99%